REFORMASI PENEGAKAN HUKUM PERSPEKTIF HUKUM PROGRESIF - Ansori, Lutfil (Jurnal Yuridis, 2017)
This articel aim for examine reformation and optimalisation of law enforcement at law enforcerment institution in terms of progresive law perspective. the law face in Indonesia today  is faced a complex problem on law enforcement process. Yet, Reformation on law enforcement is the answer to how the law in Indonesia is actuated within frame work of estabilishment an aspired state of law. Law enforcement reformation ideally must be done through legal system approach, that covered legal substance sub system, legal structure sub system, and legal culture subsystem.  in the context of  law enforcement institution reformation, institution reformation ideally based on three main orientation, which is democration principal, rule of law, and human rights. That institution reformation must be done with changing paradigm from the way of textual legal thinking to progresive legal thinking. It can be formed if reformation of law enforcement institution, consistent in bringing about changing cultural aspect that comes from changing structural aspect and instrumental aspect.